2014
DOI: 10.1007/jhep10(2014)032
|View full text |Cite
|
Sign up to set email alerts
|

Ortho-positronium observation in the Double Chooz experiment

Abstract: The Double Chooz experiment measures the neutrino mixing angle θ 13 by detecting reactorν e via inverse beta decay. The positron-neutron space and time coincidence allows for a sizable background rejection, nonetheless liquid scintillator detectors would profit from a positron/electron discrimination, if feasible in large detector, to suppress the remaining background. Standard particle identification, based on particle dependent time profile of photon emission in liquid scintillator, can not be used given the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…As an illustration of possible bias due to the spectral shape, two values could be compared: the value Q H =0. 122 assumption of the allowed shape and used in earlier review [3] for 87 Rb evaluation is twice as large as the value in Tab. 1 calculated using the corrected shape.…”
Section: Long-lived Radiogenic Elementsmentioning
confidence: 89%
See 2 more Smart Citations
“…As an illustration of possible bias due to the spectral shape, two values could be compared: the value Q H =0. 122 assumption of the allowed shape and used in earlier review [3] for 87 Rb evaluation is twice as large as the value in Tab. 1 calculated using the corrected shape.…”
Section: Long-lived Radiogenic Elementsmentioning
confidence: 89%
“…14 Wipperfurth et al recently reported the results of their high precision study of the mass ratio in [68], which they found to be M(Th)/M(U)=3.776 +0. 122 −0.075 . We use a commonly accepted value of 3.9 throughout the text, as it has been used in all experimental publications until now, and it is still compatible with the value of Wipperfurth et al within the 1σ uncertainty.…”
Section: Models Of the Earthmentioning
confidence: 99%
See 1 more Smart Citation
“…The Daya Bay Collaboration first reported a successful measurement of mixing angle θ 13 (with a statistical significance of 5.2σ) in 2012 [1] and the RENO Collaboration reported their results (with a statistical significance of 4.9σ) in the same year [2]. More precise results from reactor neutrino experiments were reported in [7][8][9]. To compensate the limitation on the source of electron antineutrinos from nuclear power plants and to reduce systematic uncertainty in estimating absolute neutrino flux from nuclear power plants, Daya Bay and RENO utilized the design of identical detectors placed in group of near and far away from the nuclear reactors.…”
Section: Introductionmentioning
confidence: 95%
“…The Daya Bay result for θ 13 reported in [1] was obtained by minimizing a χ 2 function, as was done by the other short-baseline neutrino oscillation experiments. The function used by the Daya Bay Collaboration [9] was,…”
Section: Reanalysis Of Daya Bay Datamentioning
confidence: 99%